A comunicação entre fisioterapeutas e sujeitos com encefalopatia crônica não progressiva - Bortagarai, Francine Manara (2011)
This work presents an investigation of the way physiotherapists perform their communication with subjects with chronic non-progressive encephalopathy (CNPE) having restricted or absent speech. For this purpose, we interviewed twelve physiotherapists about non-verbal communication and then we interviewed the five physiotherapists who knew and used the alternative and augmentative communication (AAC) in therapy about the use of this resource. After the initial reading of the narratives, we noticed that all the physiotherapists consider non-verbal communication important and perform it, mainly through reading facial and body expressions. Concerning the use of AAC, the five professionals of the sample emphasized the importance of this resource, although only one of them makes use of it routinely. We conclude that the physiotherapists strive to invest in non-verbal communication and/or AAC with CNPE subjects who present restricted or absent speech and that such an investment improves the hospitalization outcomes and the interaction between the subjects and the professionals who treat them. However, the theoretical and practical learning of non-verbal communication and ACC seems flawed and inadequate in physiotherapy undergraduate course. This fact can be considered one of the causes of the poor use of non-verbal communication as well as one of the causes of the lack of knowledge or of the non-routine use of AAC in therapy. The results suggest the need to overcome the purely biomedical model in the formation of the physiotherapist and to adopt some training that seeks to humanize and promote quality in physical therapy services.